Synthesis, structure and reactivity of aliphatic primary nitrosamines stabilized by coordination to [IrCl5]2– - Di Salvo, Florencia (2008)
In the present work the formation of several primary aliphatic coordinated nitrosamines by reaction of the extremely reactive K[IrCl5(NO)] in acetonitrile solution with the corresponding amine is described. Complete characterization, including X-ray diffraction determinations for some examples, are reported, and experimental evidence of their stability. Density functional theory calculations (DFT) helped to understand the role of the coordination environment of these complexes and to support, with excellent correlation with the experimental data, the proposed reaction pathways and stability studies. Complexes containing the highly unstable primary nitrosamines as ligands are generally scarce, and moreover, to our knowledge, our group has recently reported the first examples of isolated primary nitrosamines coordinated to the metal center only through the NO moiety.